EVALUASI KEANDALAN BANGUNAN DITINJAU DARI PERSYARATAN KESEHATAN DAN KENYAMANAN RUMAH SUSUN BIDARA CINA - Abila, Ainun Mardhyah; Ramadhan, M. Agphin; Purnomo, Adhi (LPPM, Universitas Negeri Jakarta, 2023)
This research aims to determine the level of health and comfort based on Minister of Public Works Regulation Number 29 of 2006 concerning Guidelines for Technical Building Requirements for Bidara Cina Flats. The method used is descriptive research using a quantitative approach. The population in this study were families who lived in flats. The sampling technique used a formula developed by Isaac and Michael to obtain 194 samples. The results of this research show that the perception of the residents of the Bidara Cina Flats regarding health, with a percentage of 72.075%, can be said to be that the level of health in the Bidara Cina Flats is Medium. It is shown based on the results of each aspect of health, namely the ventilation system, lighting system, sanitation, and The use of building materials in Block II is better than in Block I. Then the occupants' perception of comfort in the Bidara Cina Flats is still considered moderate, with a percentage of 66.355%. This is shown based on the results of each aspect of comfort, including movement space, air condition, sight (visual), sound (audio), and social environment in Block II are better than in Block I.